TRAINING ON THE IMPORTANCE OF DIGITAL PORTFOLIOS FOR PRIVATE CAMPUS STUDENTS - Nasution, Hafifah; Wiradendi Wolor, Christian; Takidah, Erika; Hamidah, Hamidah; Saptono, Ari; Purwohedi, Unggul; Iranto, Dicky; Muhammad Zairin, Gentiga (Yayasan Education and Social Center, 2023)
This community service activity aims to increase the understanding of partners related to CV and increase expertise in making digital portfolios. This activity was preceded by analyzing the current situation faced by the partners. From the results of this analysis, the team concluded that a training activity related to the importance of digital portfolios for students was needed. The partners of this community service activity are students who are studying at Universiti Sabah Malaysia and Jakarta State University. This activity was done online via the Zoom application on Monday, July 10th 2023. Based on the evaluation results of this activity, students' understanding and abilities had increased about digital portfolio creation